Teaching Speaking Using Conversation In The novel ForThe Eight Grade Students of SMP Muhammadyah 10Surakarta - Sajdah Laily, Nissa, Anam Sutopo, S. Pd., M. Hum., Dr (2016)
This research aims at describing the implementation of teaching speaking using conversation in the novel for the eight grade students of SMP Muhammadyah 10 Surakarta. The objectives of the research is to describe the procedure of teaching speaking using conversation on the novel, the effectiveness of teaching speaking using conversation in the novel, and the strenght and weaknesses of teaching speaking using conversation in the novel. The subject of this study is the English teacher and the eight grade students of SMP Muhammadyah 10 surakarta.. the methods of collecting data are observation, document analysis, and interview. In analyzing the data, the writer uses an interactive model, namely, data reduction, data display and verification of data.. Based on the research finding, there are three steps of the implementation of teaching speaking using conversation in the novel, while the procedures to teaching speaking are; 1.) opening 2.) main activity 3.) closing. This research is quite effective because there is a significance increase in students score of using conversation in the novel. It is proved by using calculation of T-test formula as follows: the result of Ttest shows that there is no significance difference between pre-test and post-test I which is shown with the significance value 0,717>0,05 but there is a difference between post-test I and post-test II with the significance value 0,000<0,05 and there is also a difference in the post-test II and post-test III has been shown with the significance value 0,000<0,05. So, it can be conclude that there is a significance increase in teaching speaking using conversation in the novel. It is proven that the student's score of speaking thaught using conversation in the novel is better. It means that the use of conversation in the novel in teaching speaking is quite effective. The strenght of this research is teaching is enjoyable and students learn something new, while the weaknesses is there is a lack of time in teaching speaking and limited of novel collection.